Islamic Microfinance and Cultural Synergy: A Catalyst for Women’s Economic Independence in Sandi Morse MSMEs - Purnamasari, S; Zainul, M; Rozak, Purnama; Huzaini, Huzaini (Mimbar Agama Budaya, 2024)
The main agenda of the UN Sustainable Development Goals (SDGs) and the African Union (AU) Agenda 2063 is to end poverty and inequality in all its forms without exception through the economic empowerment of women. The broad geographical and cultural conditions as well as the demographic conditions of society, especially MSME actors who are dominated by women and have various levels of knowledge (education, knowledge) must be the main focus. This research answers the potential for using the Islamic financing model as a tool to increase the capacity of women's empowerment and what are the obstacles to financial independence for women in Morse Indah MSMEs. This research is qualitative research with a case study approach and descriptive analytical data analysis techniques. The results of this research are that microfinance institutions have a model in the form of providing access to financial services for women such as financing and business savings through training models in management and business development opportunities. Based on the curation of analysis and research findings, the obstacles are problems in the field of access to financing, and the encouragement of digitalization/onboarding of MSMEs for women/expansion of marketing through digitalization.